Shock hipovolémico intra y posparto, factores de riesgo y morbimortalidad en gestantes atendidas en el servicio de gineco obstetricia del Hospital Regional Isidro Ayora - Alvarado Roa, Stalin Manuel (2014)
Childbirth is the physiological process by which the woman ends her pregnancy; however this may be complicated during delivery or after it. The haemorrage in the obstetric patient is extremely important and is a risk factor for mother and child. It is the leading cause of maternal death in hospitals. Obviously the woman hefty bleeding to death condition must pass before the contingency produce hypovolemic shock. Through this character study: quantitative, transversal and descriptive entitled "hypovolemic shock INTRA AND POST DELIVERY, RISK FACTORS AND MORBIDITY IN PREGNANT SERVED IN THE SERVICE OF REGIONAL HOSPITAL OBSTETRICS GYNECOLOGY ISIDRO AYORA"; the same which was a universe of 70 patients whose sample was selected taking into account the inclusion and exclusion criteria, 11 patients who met them, with the following results: The higher prevalence of obstetric hemorrhage is 0.15 500ml being the most affected patients over 35 years (54.54%), large multiparous (36.36%) and with a duration of normal labor. The main diseases associated are given by anemia, RPM, preeclampsia and hypertension with 9.09% each. The management is consistent and complies in all entities producing obstetric bleeding protocols issued by the Ministry of Public Health of Ecuador. Morbidity produce these hemorrhages is 16 per 100 deliveries; and maternal mortality is absent. The results were summarized in frequency tables and percentages for subsequent statistical analysis and graphic representation. Keywords: obstetric hypovolemic SHOKE, risk factors, obstetric hemorrhage, morbidity and mortality.